Subjective Wellness, Acute: Chronic Workloads, and Injury Risk in College Football. Issue 12 (December 2019) - Sampson, John A.; Murray, Andrew; Williams, Sean; Sullivan, Adam; Fullagar, Hugh H. K.
Abstract : Abstract: Sampson, JA, Murray, A, Williams, S, Sullivan, A, and Fullagar, HHK. Subjective wellness, acute: chronic workloads and injury risk in college football. J Strength Cond Res 33(12): 3367–3373, 2019—Acute:chronic workload ratios (ACWRs) are associated with injury risk across team sports. In this study, one season of workload and wellness data from 42 collegiate football players were retrospectively analyzed. Daily 7:21 day exponentially weighted moving average (EWMA) ACWRs were calculated, and z -score fluctuations ("normal, " "better, " and "worse") in sleep, soreness, energy, and overall wellness were assessed relative to the previous day ACWRs and considered as an interactive effect on the risk of noncontact injury within 0–3 days. Fifty-five noncontact injuries were observed, and injury risks were very likely higher when ACWRs were 2 SD s above (relative risk [RR]: 3.05, 90% confidence interval [CI]: 1.14–8.16) and below (RR: 2.49, 90% CI: 1.11–5.58) the mean. A high ACWR was trivially associated ( p < 0.05) with " worse " wellness ( r = −0.06, CI: −0.10 to −0.02), muscle soreness ( r = −0.07, CI: −0.11 to −0.03), and energy ( r = −0.05, CI: −0.09 to −0.01). Feelings of "better " overall wellness and muscle soreness with collectively high EWMA ACWRs displayed likely higher injury risks compared with " normal " (RR: 1.52, 90% CI: 0.91 to 2.54; RR: 1.64, 90% CI: 1.10–2.47) and likely or very likely (RR: 2.36, 90% CI: 0.83 to 674; RR: 2.78, 90% CI: 1.21–6.38) compared with " worse " wellness and soreness, respectively. High EWMA ACWRs increased injury risk and negatively impacted wellness. However, athletes reporting "better" wellness, driven by "better" muscle soreness presented with the highest injury risk when high EWMA ACWRs were observed. This suggests that practitioners are responsive to, and/or athletes are able to self-modulate workload activities.